Understanding the development of local government: theory and widence from the Dutch case - Raadshelders Jas C.N.
In this article, a theory on local government development based on extensive empirical research in Dutch local government is presented. Most public administration literature, both in the United States and in Europe, that focuses on the development of government and its bureaucracy deals entirely or predominantly with central government. There are various reasons why local government development merits separate attention. The time span of 400 years brings out in full how the major shifts that occured in the Netherlands from the late 19th century onward had been "prepared" since early modern times. Attention will be paid to the degree to which the Dutch case is unique as well as representative for development
Keywords: Civil Service -- Netherlands; Bureaucracy -- Netherlands; Local Government -- Netherlands